Evolutionary Insights Into Microbiota Transplantation in Inflammatory Bowel Disease - Wang, Xiaoli; Zhao, Jingwen; Feng, Yuanhang; Feng, Zelin; Ye, Yulin; Liu, Limin; Kang, Guangbo; Cao, Xiaocang (Frontiers in Cellular and Infection Microbiology, 2022)
The intestinal microbiome plays an essential role in human health and disease status. So far, microbiota transplantation is considered a potential therapeutic approach for treating some chronic diseases, including inflammatory bowel disease (IBD). The diversity of gut microbiota is critical for maintaining resilience, and therefore, transplantation with numerous genetically diverse gut microbiota with metabolic flexibility and functional redundancy can effectively improve gut health than a single probiotic strain supplement. Studies have shown that natural fecal microbiota transplantation or washing microbiota transplantation can alleviate colitis and improve intestinal dysbiosis in IBD patients. However, unexpected adverse reactions caused by the complex and unclear composition of the flora limit its wider application. The evolving strain isolation technology and modifiable pre-existing strains are driving the development of microbiota transplantation. This review summarized the updating clinical and preclinical data of IBD treatments from fecal microbiota transplantation to washing microbiota transplantation, and then to artificial consortium transplantation. In addition, the factors considered for strain combination were reviewed. Furthermore, four types of artificial consortium transplant products were collected to analyze their combination and possible compatibility principles. The perspective on individualized microbiota transplantation was also discussed ultimately.